CALCULATING BEDLOAD TRANSPORT IN RIVERS: CONCEPTS, CALCULUS ROUTINES AND APPLICATION - Macedo, Hudson de Azevedo [UNESP]; Stevaux, Jose Candido [UNESP]; Assine, Mario Luis [UNESP]; Silva, Aguinaldo; Pupim, Fabiano do Nascimento; Merino, Eder Renato [UNESP]; Lo, Edward (Uniao Geomorfologia Brasileira, 2017)
Rivers are immensely important to human activities such as water supply, navigation, energy generation, and agriculture. They are also an important morphodynamic agent of erosion, transport and deposition. Their capacity to transport sediment depends on their hydraulic characteristics and can be predicted by mathematical models. Several mathematical models can be used to compute bed-load transport. Each one is appropriately better for certain conditions. In this paper, we present an application built in Microsoft Excel to compute the bed-load transport in rivers based on the Van Rijn mathematical model. The Van Rijn model is appropriate for rivers transporting sandy sediments in conditions of subcritical flow. Hydraulic parameters such as channel slope, stream power, and Reynolds and Froude numbers can be calculated using the application proposed here. The application was tested in the Parana River and results from the calculations are consistent with data obtained from fieldwork surveys. The error of the application was only 20%, which shows good agreement of the model with survey values.
Keywords: Bed-Load Transport; Van Rijn; Mathematical Model; Microsoft Excel; Parana River